Current trends in radiocarbon in Skagerrak and Kattegat assessed by brown algae from Swedish coastal waters - Eriksson Stenström, Kristina; Mattsson, Sören (Radiation Protection Dosimetry, 2025)
Carbon-14 often dominates the effective dose to the public from authorized discharges from Swedish nuclear power plants (NPPs). In contrast to air-borne releases, water-borne discharges of 14C are currently not routinely monitored at Swedish NPPs. We have measured 14C in Fucus spp. (brown algae, used as bioindicators of 14C) in shallow waters at the Swedish west coast from 2020 to 2024. At Ringhals NPP, 14C in Fucus spp. was up to ~50% higher than at nearby marine reference sites and was also higher than observed in the nearby terrestrial environment. The local marine environment of Ringhals NPP showed high spatial and temporal variability in 14C. Carbon-14 in Fucus spp. was generally higher in Skagerrak than in the more southernly Kattegat, likely mainly due to influence from discharges from the spent nuclear fuel reprocessing plant in La Hague in France and from its counterpart in Sellafield in the UK.